Restriction Digest And Electrophoretic Analysis Of Mitochondrial Genome From Jamnapari Goats - A. Reenaa, Joys Andas. (Universiti Malaysia Sarawak, 2010)
Jamnapari is one of the domestic goats with a dual purpose whereby it is well known for high milk and meat production. As a preliminary step in establishing commercialization protocols for genotyping of the Jamnapari goats, DNA samples from these sources were tested for their feasibility in producing quality basic data in the lab and to obtain a gross profile of mitochondrial DNA (mtDNA) of Jamnapari goats. Hence, this study used simple strategies such as Restriction Endonucleases (RE) digestion and Agarose Gel Electrophoresis (AGE) to obtain the gross profile of cytochrome b (cyt b) ofmtDNA from Jamnapari goat. The mitochondrial cyt b sequences of the goat samples were amplified by PCR using Universal Primer CYT bl and CYT b2. PCR products of 359-bp were successfully obtained from the cyt b gene of these investigated samples. The differences observed between the investigated samples was detected by restricting the amplified product with RE. Hinf I RE were identified as potential RE to differentiate the investigated goat samples.